Pediatric tracheostomy care updates. Issue 6 (December 2020) - Smith, Matthew M.; Benscoter, Dan; Hart, Catherine K.
Abstract : Purpose of review: The aim of this review is to provide an update on the management of pediatric tracheostomies. Recent findings: Recent literature has focused on optimization of care for children with tracheostomies including prevention and management of skin breakdown, timing of tracheostomy tube changes, the role of multidisciplinary and team-based approaches to education and management of tracheostomy patients, ideal timing of surveillance endoscopy, and the emerging role of telemedicine in the care of tracheostomy patients. Summary: A focus on quality improvement and a systematic, team-based approach to care has the potential to improve the quality of care for pediatric tracheostomy patients.